Tahlīlu Bunūd Ikhtibārāt Mahārah al-Qirā’ah fī al-Kitāb “al-Ikhtibārāt al-Lugawiyyah” fī Ḍau’i Taṣnīf Blūm fī Mustawiyāt al-Majāl al-Ma’rīfī: Analysis of the Reading Ability Test in The Book al-Ikhtibārāt al-Lugawiyyah According to Bloom's Theory in the Cognitive Domain - Mahmudi, Ihwan; Solihah, Dwi Aprilia; Rahmawati, Zakiya Setyo (Aphorisme: Journal of Arabic Language, Literature, and Education, 2023)
The purpose of this research is to know the benefits of reading and to determine the level of suitability of the questions regarding reading ability in the book Ikhtibarat Allughowiyah based on Bloom's theory. The research method used is the library research methodology with literacy data sources related to analyzing the language test in reading skills in light of Bloom's classification. Data is collected from written data sources such as books, periodicals, and scientific research. Data Analysis with stages of data reduction, data presentation, and drawing conclusions or verification. The research results show that the benefits of reading are education, gaining life experiences, knowing a range of events, following the development of science and technology, and enhancing and enriching cultural knowledge. The test items were concentrated in the lower levels (remembering, understanding, and application) at a rate of (72.73%). In comparison, the test items at the higher levels (analysis, synthesis, and evaluation) were represented by a small percentage that did not exceed (27.27%) only.